Standardizing Psychological Steadfastness Scale for Primer Soccer League Referee - Ismael, Huida; Salman, Mohammed (Journal of Physical Education, 2018)
Standardizing Psychological Steadfastness Scale for Primer Soccer League RefereeThe individuals’ abilities to face difficulties differ according to their ability to adapt to these changes. Steadfastness is related to the ability to change and in the field of sports athletes can benefit from positive psychological pressures and improving to face these changes.The importance of the research lies in identifying psychological steadfastness in soccer league referees according to correct scientific bases to uplift the level of referees’ selection. Thus the researchers aimed at standardizing a scale for psychological steadfastness scale for new referees. The researcher used a descriptive method on 140 referees for the season 2016 – 2017. The results of the research lead to specifying criteria for steadfastness scale and recommended using these criteria and standards in selecting soccer referees.